Barriers and drivers to the adoption of energy-efficient technologies in the building sector: a survey in Brazil - Cristino, Talita Mariane [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Energy is one of the most important factors for the growth of the world economy, thus the demand for it has increased over the years. Such a growing brings, among several issues, environmental impacts, mainly the increase of greenhouse gas emissions. For decades, the industrial sector was responsible for the greatest part of the energy demand, but as time went by the consumption shifted toward the building sector, which is responsible for 36% of the global final energy consumption and 40% of the total greenhouse gas emissions. Brazil, as well as worldwide, has been facing increasing energy consumption in the building sector. Such a scenario suggests urgency in reducing energy consumption. A way to reach this goal, without affecting the occupants’ welfare, is the adoption of building energy-efficient (BEE) technologies. There are several of these technologies available, bringing lots of benefits. However, there are barriers that hinder their adoption. Thus, before overcoming such barriers, it is necessary to know them. Therefore, the aim of this research is to identify the barriers that hinder the adoption of energy-saving technologies in the Brazilian building sector, and propose strategies to overcome them. To achieve such an objective, this research carried out a literature review over more than 450 articles gathered from the SCOPUS database, and 27 barriers were found to the adoption of energy-efficient technologies, which was classified into 6 groups, named as Financial/Economic; Market; Technological; Professional/Technical; Governmental/Political/Regulatory; and Cultural/Social/Behavioral. Such barriers were submitted to the judgment of Brazilian experts in order to capture their relevance to the national reality, by means of a structured questionnaire. A total of 1000 questionnaires were answered by professionals registered on the LinkedIn social network who had some academic education or professional experience related to building energy efficiency. Then, based on such questionnaires, a cluster analysis and factor analysis was performed in order to confirm the taxonomy proposed by the literature review, classifying at the same time, the categories according to their importance. The results confirmed the taxonomy proposed by the literature review, and the Governmental/Political/Regulatory and Financial/Economic barriers were the groups more important, according to the perception of the Brazilian experts. Furthermore, some strategies to overcome such barriers were proposed based on literature. Therefore, it is worth highlighting the main scientific contribution of this research is the theoretical consolidation on the barriers to the adoption of BEE technologies in the Brazilian building sector, in addition to presenting strategies to overcome them. It is worth noting that these contributions helped to fill scientific gaps related to the theme, which was presented in the research justification. As a practical contribution, the results of this research can be useful for the formulation of public policies, since it identified the barriers that most hinder the adoption of BEE technologies in Brazil. As these barriers are ranked in importance, it will be easy to start developing actions and programs focused on overcome the most important categories of barriers.

A energia é um dos fatores mais importantes para o crescimento da economia mundial, portanto, a demanda por ela vem aumentando ao longo dos anos. Esse crescimento traz, entre várias questões, alguns impactos ambientais, principalmente o aumento das emissões de gases de efeito estufa. Durante décadas, o setor industrial foi responsável por grande parte da demanda de energia, mas com o passar do tempo, o consumo passou para o setor de edificações, que é responsável por 36% do consumo final global de energia e 40% do total de gases de efeito estufa emissões. O Brasil, assim como em todo o mundo, vem enfrentando um aumento no consumo de energia no setor de edificações. Esse cenário sugere urgência na redução do consumo de energia. Uma maneira de atingir esse objetivo, sem afetar o bem-estar dos ocupantes, é a adoção de tecnologias energeticamente eficientes em edificações. Existem várias tecnologias energeticamente eficientes disponíveis que trazem muitos benefícios ao setor de edificações. No entanto, existem barreiras que impedem sua adoção. Assim, antes de superar essas barreiras, é necessário conhecê-las. Portanto, o objetivo desta pesquisa é identificar as barreiras que impedem a adoção de tecnologias energeticamente eficientes no setor de edificações no Brasil, e propor estratégias para superá-las. Para atingir esse objetivo, esta pesquisa realizou uma revisão da literatura em mais de 450 artigos reunidos na base de dados SCOPUS, e foram encontradas 27 barreiras à adoção de tecnologias energeticamente eficientes em edificações, classificadas em 6 grupos, denominados Financeiro/Econômico; Mercado; Tecnológico; Profissional/Técnico; Governamental/Político/Regulatório; e Cultural/Social/Comportamental. Tais barreiras foram submetidas ao julgamento de especialistas brasileiros, a fim de capturar a sua importância para a realidade nacional, por meio de um questionário estruturado. Um total de 1000 questionários foram respondidos por profissionais inscritos na rede social LinkedIn, que possuiam alguma formação acadêmica ou experiência profissional relacionada à eficiência energética em edificações. Em seguida, com base nesses questionários, os dados foram analisados por meio da análise de cluster e análise fatorial, a fim de confirmar a taxonomia proposta pela revisão da literatura, classificando ao mesmo tempo as categorias de acordo com sua importância. Os resultados obtidos confirmaram a taxonomia proposta pela revisão da literatura, e os grupos Governamental/Político/Regulatório e Financeiro/Econômico foram considerados mais importantes, segundo a percepção dos especialistas brasileiros. Além disso, algumas estratégias para superar essas barreiras foram propostas com base na literatura. Destaca-se, portanto, que a principal contribuição científica desta pesquisa é a consolidação teórica das barreiras à adoção de tecnologias BEE no setor de edificações no Brasil, além de apresentar estratégias para superá-las. Cabe ressaltar que essas contribuições ajudaram a preencher lacunas científicas relacionadas ao tema, apresentadas na justificativa da pesquisa. Como contribuição prática, os resultados desta pesquisa podem ser úteis para a formulação de políticas públicas, uma vez que a pesquisa identificou as barreiras que mais impedem à adoção de tecnologias energeticamente eficientes no Brasil. Como essas barreiras são classificadas em importância, será fácil começar a desenvolver ações e programas focados em superar os grupos de barreiras mais importantes.
Barreiras e drivers a adoção de tecnologias energeticamente eficientes no setor de edificações: um survey no Brasil
Keywords: Energy efficiency; Building energy efficiency; Energy-saving technologies; Energy-efficient technologies; Barriers; Strategies; Energia - Consumo; Energia - Políticas públicas; Produção de energia elétrica; Inovações tecnológicas; Eficiência energética